Microcomputers for development : issues and policy - Munasinghe, Mohan,ed. (CINTEC-NAS ColomboLK, 1985)
Contains three papers on the reasons for, the development, and content of a computer policy for developing countries. Discusses the microcomputer in service of developmet and defines computer policy issues. Discusses use of microcomputers in the agricultural, energy and health sectors in developing countries. Contains abstracts of agricultural, energy, and health sector papers. Also includes general abstracts on international data communications and microcomputer applications.